Evaluation of four commercial COVID-19 diagnostic RT-PCR kits used in Libya (Journal of Medical Sciences, 2023)
Background: Real-time reverse transcriptase chain reaction is considered the most sensitive and specific assay for COVID-19 detection. This study was planned to compare and evaluate four commercially diagnostic kits. Material and methods: 92 Nasopharyngeal swabs collected from different symptomatic patients were studied in this project. The total nucleic acid (RNA) was extracted, and RT-PCR was done using four commercial diagnostic kits from different manufacturers, DANN and BGI (China), Hibrigen, and Bio-speedy (Turkey). Result: Although all 92 clinical samples were subjected to the same four diagnostic kits, the results revealed variations in the performance. The total number of positive cases was (42/92) for Da An Gene, BGI (36/92), Bio-speedy (31/92), and Hibrirgen (14/92).